Female sex, atrial fibrillation, and heart failure, but not ageing, are associated with endomysial fibrosis in atrial myocardium: results from the CATCH ME consortium. (24th May 2021) - Winters, J; Zeemering, S; Isaacs, A; Casadei, B; Fabritz, L; Guasch, E; Mont, L; Hatem, S; Kirchhof, P; Sinner, MF; Stoll, M; Verheule, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): CATCH ME Horizon 2020, EU-H2020-PHC-RIA (633196) CVON2014-09, RACE V: Reappraisal of Atrial Fibrillation: Interaction between hyperCoagulability, Electrical remodeling, and Vascular Destabilisation in the Progression of AF Background: Atrial fibrosis is one of the most important aspects of structural remodeling in the atria and largely increases the inducibility and sustainability of AF. The main risk factors for recurrent AF, such as ageing, heart failure, and history of AF, partly enhance AF propensity by inducing atrial fibrosis. A distinction should be made between replacement fibrosis following myocyte death and reactive fibrosis, which often occurs in the absence of myocyte death.  Endomysial fibrosis, a type of reactive fibrosis in between cardiomyocytes, is  poorly studied as a result of limitations and labor intensiveness of traditional histochemical quantification. Purpose: We examined the contributions of age, sex, AF and heart failure to the development of overall and endomysial fibrosis in the context of concurrent pathologies. Methods: We developed an algorithm for automated quantification of multiple features of structural remodeling following myocardial staining with wheat germ agglutinin (WGA).  We studied the type, quantity and distribution of fibrosis in left (LAA, n = 95) and right (RAA, n = 76) atrial appendage biopsies in a large European cohort of patients with varying indications for cardiac surgery. Linear mixed effect models were constructed to predict endomysial fibrosis quantity and clustering as a function of AF, heart failure, sex, age and 4 principle components that accounted for potential confounding due to other clinical characteristics. Results: Persistent AF, heart failure and female sex were independently associated with endomysial fibrosis, age was not. AF and age were not associated with overall fibrosis. Clustering of endomysial fibrosis was observed in females (LAA), paroxysmal AF (RAA), persistent AF and heart failure (LAA) patients (table 1).  Conclusions: Female sex, AF, and heart failure are associated with the quantity and distribution of endomysial fibrosis, the effects of age are limited.